Social Media Influence and Investment Decision: Mediate Role of Investors' Sentiment - Kapil Khanal; Shiva Raj Poudel; Subhadra Dahal; Birendra Kunwar (Contemporary Research: An Interdisciplinary Academic Journal, 2026)
This study investigates that how social media influence on investment decision in Nepali capital market by the mediating variable of investor sentiment. The research followed descriptive and causal comparative research designs, and the data were collected from the 174 active investors. The results indicated that the social media platform has a significant effect in investor sentiment and this has in turn effect in investments. The results indicated that there was a strong and positive correlation between the factors of social media influence and investor sentiment (β = 0.760), and between social media and investment decisions (β = 0.388). Similarly, investor sentiment also showed a significant positive effect on investment decisions (β = 0.289). Moreover, the indirect effect of the social media on the investors' decision through the mediator investor sentiment was significant (β = 0.219), which implies that this effect is partially mediated. The study found that social media is not just a source of information, but also influences investors' emotional and behavioral reactions that in turn drive their investment decisions. The results indicate the increasing behavioral and psychological role of digital media in the financial markets, especially emerging markets like Nepal where investor education and regulation are still in their infancy.